URGENSI PILIHAN HUKUM TERKAIT PEMBAGIAN WARISAN BERDASARKAN HUKUM ISLAM - Cahyaningtyas, Kartika; Mahfudi, Nafi’uddin Fauzi (LPPM institut Teknologi Bisnis AAS Indonesia, 2023)
This study examines and analyzes the legal options chosen to determine the distribution of the inheritance from the late Mulrejo or Simpar to the heirs in which the wishes of the heirs of the late Mulrejo or Simpar divide equally in accordance with the provisions of the Civil Code which in fact the heir and all other heirs are Muslim who the distribution of inheritance should be based on Islamic law. The method used with normative research with research results is the distribution of inheritance from the late Mulrejo or Simpar by using the concept of hilah which is divided by the provisions of Islamic law, after that the heirs who get more shares give to heirs who get less with the willingness and how to donate. This is in accordance with the wishes of the heirs to divide the inheritance equally. The role of the Notary is needed when making a Certificate of Inheritance which explains that the distribution with the hilah concept which divides based on Islamic law after that is in accordance with the wishes of the heirs who want to divide equally in accordance with the Civil Code. This is because a Certificate of Inheritance can be made before a Notary. Keywords: choice of law, division of inheritance, Hilah concept, Notary